Detection and analyses of latent DNA. (December 2022) - Linacre, Adrian; Petcharoen, Piyamas
Abstract: Latent DNA detection has the potential to transform aspects of DNA collection at scenes and from items. In the absence of being able to visualise the location of cellular material, all collection of samples at crime scenes is currently performed blind. With the advent of the application of a nucleic acid staining dye, the DNA within skin cells (commonly called keratinocytes and corneocytes) can be visualised. Diamond Dye fluoresces when it binds to the backbone of DNA. This fluorescence can be recorded using a simple mini-microscope allowing the location and number of cells to be recorded. The potential to visualise cells on a wide range of substrates opens the possibility to target sample collection and to triage samples for further analyses to only those containing DNA. Diamond Dye has been found to be safe at the concentration used, inexpensive, available commercially, easy to apply, is highly sensitive, and does not inhibit further analyses such as PCR. This work presented at the ISFG congress gives an overview of the current developments on using DNA staining dyes to record the number of cells present on a wide range of substrates. It is essential to firstly understand the composition of cellular material deposited by touch, where it originates and the relative composition of corneocytes and cell-free DNA. Insight into the origins of touch DNA will be presented along with the staining of nuclei using a range of dyes to show corneocyte degradation. The presentation will cover how DNA binding dyes can be used to effectively triage sample collection, monitor cell collection using different swabs and tapes.